Seasonal Change of Difference Between the Ground-based and EP-TOMS Satellite Ozone Measurements - Kulinich, B.V.; Evtushevsky, A.M.; Leonov, N.A.; Milinevsky, G.P. (Український антарктичний журнал, 2005)
The relative differences between the total ozone data from the Vernadsky Station and EP-TOMS satellite spectrometer are analyzed. The 2000-2003 period is considered. To estimate the cloudiness influence on data disagreement, comparison was made taking into account the conditions of cloud cover over station. The daily Dobson spectrophotometer measurements were selected to form the data files of “cloudy days” and “cloudless days”. Mean relative differences of -0.6% and 6.9% were obtained for cloudy and clear sky, respectively. Seasonal changes of the data disagreement are different for cloudy and cloudless days. Observations in cloudy conditions show maximum positive difference in summer and negative one in the early spring and later autumn. In cloudless conditions TOMS-Dobson difference changes with some ascending trend. This analysis confirms the results of previous comparison of the EP-TOMS and Vernadsky ozone data for 1996-2000. The overestimation of the ground-based total ozone by the TOMS values in the clear sky conditions is perhaps caused by an erroneous interpretation of the snow covered surface reflection as the cloudiness one in the TOMS ozone retrieval algorithm. Проведен анализ относительных разностей между данными измерений общего содержания озона в атмосфере на станции Академик Вернадский и спутниковым спектрометром EP-TOMS. Рассматривается период 2000-2003 гг. Для того, чтобы оценить влияние облачности на расхождение данных, сравнение выполнялось с учетом состояния облачного покрова над станцией. Ежедневные измерения со спектрофотометром Добсона отбирались в отдельные ряды данных “облачные дни” и “безоблачные дни ”. Средние относительные разности составляют –0.6% и 6.9%, соответственно, для облачного и ясного неба. Есть отличия сезонного хода разности для облачных и безоблачных дней. При условиях облачности существует положительная разность летом и отрицательная весной и осенью. В условиях безоблачного неба разность TOMS-Добсон изменяется в среднем с некоторым восходящим трендом. Данный анализ подтверждает результаты предыдущего сравнения озоновых данных EP-TOMS и станции Вернадский за 1996-2000 гг. Завышения содержания озона в данных EP-TOMS по сравнению с наземными, которое имеет место в условиях чистого неба, вероятно, связано с ошибочной интерпретацией отражения от поверхности, покрытой снегом, как отражения от облаков в алгоритме TOMS для определения озона. Проведено аналіз відносних різниць між даними вимірювань загального вмісту озону в атмосфері на станції Академік Вернадський та супутниковим спектрометром EP-TOMS. Розглядається період 2000-2003 рр. Для того, щоб оцінити вплив хмарності на розбіжність даних, порівняння виконувалося з урахуванням стану хмарного покриву над станцією. Щоденні вимірювання із спектрофотометром Добсона відбиралися в окремі ряди даних “хмарні дні” та “безхмарні дні”. Середні відносні різниці становлять –0.6% та 6.9%, відповідно, для хмарного та ясного неба. Є відмінності сезонного ходу різниці для хмарних і безхмарних днів. За умов хмарності існує позитивна різниця влітку і негативна навесні та восени. В умовах безхмарного неба різниця TOMS-Добсон змінюється в середньому з деяким висхідним трендом. Даний аналіз підтверджує результати попереднього порівняння озонових даних EP-TOMS та станції Вернадський за 1996-2000 рр. Завищення вмісту озону в даних EP-TOMS порівняно з наземними, яке має місце в умовах чистого неба, ймовірно, пов'язане з помилковою інтерпретацією відбиття від поверхні, покритої снігом, як відбиття від хмар в алгоритмі TOMS для визначення озону.